Comparison of Microleakage and Thickness of Resin Cement in Ceramic Inlays with Various Temperatures - Homayoun Alaghemand; Faezeh Abolghasemzadeh; Farzaneh Pakdel; Reza Judi Chelan (Tabriz University of Medical Sciences, 2014)
Background and aims. Microleakage is still one of the major problems of composite-based restorations. This study compared the microleakage and thickness of resin cement in ceramic inlays with various temperatures. Materials and methods. Class V cavities were prepared on the buccal and lingual aspects of thirty human molars with occlusal margins in enamel and gingival margins in dentin (3 mm wide, 5 mm long and 2 mm deep). Laboratory-made inlays (LMI) were used for buccal cavities, and CAD/CAM inlays (CMI) were used for lingual cavities. All the cavities were divided into six groups (n=10): 1) LMI at -5°C; 2) LMI at 50°C; 3) LMI at room temperature (25°C); 4) CMI at -5°C; 5) CMI at 50°C; 6) CMI at room temperature (25°C). Inlays were bonded to cavities in a pulp pressure- and temperaturesimulating device. After thermocycling and dye penetration, the teeth were divided into two mesiodistal halves. Amount of dye penetration and film thickness were measured under a stereomicroscope and analyzed with Kruskal-Wallis, Wilcoxon and Spearman's correlation tests ( = 0.05). Results. There were no statistically significant differences in leakage between different inlay temperatures (P > 0.05). The mean cement thickness in laboratory-made inlays (gingival margin, 83.7 ± 11 and occlusal margin, 84.7 ± 19) was greater than that in CAD/CAM inlays (gingival margin, 69 ± 16 and occlusal margin, 84.7 ± 16). No correlation was found between cement thickness and microleakage either in enamel or dentin for any of the ceramic systems. Conclusion. Differences in inlay temperature had no effect on microleakage. CAD/CAM inlays had lower cement thickness than laboratory-made inlays, but this was not related to their microleakage.